Discovering “Place” and “Space” in Psalm 104: Festschrift for GTM Prinsloo - de Claisse-Walford, Nancy (Journal for Semitics, 2023)
Taking cues from Gert Prinsloo’s work on “space” and “place” and employing a canonical reading of the book of Psalms, this article attempts to find the “space” and “place” of Ps 104. Psalm 104 is located in Book 4, which, according to the story-line of the Psalter, reflects the exilic period of Israel’s history. After introducing the psalm and examining its provenance, the article moves on to a detailed study of “place” and “space,” using Claudia Camp’s categories of “firstspace,” “secondspace,” and “thirdspace,” and employing “Chatman’s Box” to further define “secondspace” and “thirdspace.” The article concludes that the words of Ps 104, directed to exilic and postexilic hearers, were a reminder that God is sovereign over and provides for all creation, and as part of the created order, humanity should recognise God’s provision for it despite life
free
Keywords: Psalm 104; canonical; creation; place; space